Systems and conceptual design of a train cab front cleaning robot - Tomiyama, Tetsuo; García, Luis Rubio; Kršlin, Andraž; Taykaldiranian, Gerard (Elsevier, 2017)
This paper presents and briefly describes the methodology used to get the systems and conceptual design of a train cab front cleaning robot. While the sides of the trains are cleaned by a mechanised washer, the cab fronts are cleaned manually which imply a number of health and safety issues. The aim of this project is first to carry out an analysis of the current procedures in order to detect the possible gaps in the process, generating a list of requirements that will make possible the conceptual design of a cleaning system that fulfil those requirements. The proposed solution includes the division of the system in various subsystems where different solutions for each subsystem will be considered, analysed and selected as a final option to develop a prototype. This paper focuses in the main structure of the robot that holds the end-effector; different conceptual designs are shown that comply with the requirements set in the systems design.
Keywords: Cleaning robot; systems design; conceptual design; product development